Removal of per- and polyfluoroalkyl substances (PFAS) from water using magnetic cetyltrimethylammonium bromide (CTAB)-modified pine bark - Zhang, Ruichi; Ren, Zhongfei; Bergmann, Ulrich; Uwayezu, Jean Noel; Carabante, Ivan; Kumpiene, Jurate; Lejon, Tore; Levakov, Ilil; Rytwo, Giora; Leiviskä, Tiina (Journal of Environmental Chemical Engineering, 2024)
Per- and polyfluoroalkyl substances (PFAS) have gained global attention in recent years due to their adverse effect on environment and human health. In this study, a novel and cost-effective sorbent was developed utilizing forestry by-product pine bark and tested for the removal of PFAS compounds from both synthetic solutions and contaminated groundwater. The synthesis of the adsorbent included two steps: 1) loading of cetyltrimethylammonium bromide (CTAB) onto the pine bark and followed by 2) a simple coating of magnetite nanoparticles. The developed sorbent (MC-PB) exhibited 100 % perfluorooctanoic acid (PFOA) and perfluorooctanesulfonic acid (PFOS) removal from synthetic solution (10 µg/L PFOA and PFOS) and enabled quick magnetic separation. A rapid removal of PFOA (> 80 %) by MC-PB was observed within 10 min from synthetic PFOA solution and the adsorption equilibrium was reached within 4 h, achieving > 90 % removal of PFOA (dosage 2 g/L, PFOA 10 mg/L, initial pH 4.2). The PFOA adsorption kinetics fitted well to an optimized pseudo-order model (R2=0.929). Intra-particle diffusion and Boyd models suggested that the adsorption process was not governed by pore diffusion. The maximum PFOA adsorption capacity was found to be 69 mg/g and the adsorption isotherm was best described by the Dual Mode Model (R2=0.950). The MC-PB demonstrated > 90 % PFOA and PFOS removal from contaminated groundwater. Furthermore, both short- and long-chain perfluorosulfonic acids and 6:2 fluorotelomer sulfonate were efficiently removed resulting in 83.9 % removal towards total PFAS (2 g/L dosage). Validerad;2024;Nivå 2;2024-09-17 (sofila); Funder: Regional Council of Lapland, Troms og Finnmark County Municipality; Full text license: CC-BY 4.0 Sustainable management of PFAS- contaminated materials